Chaihuang Qingyi Huoxue granule ameliorates severe acute pancreatitis by modulating gut microbiota and repairing the intestinal mucosal barrier - Zhang, Xiaobin; Zeng, Xusen; Guo, Wen; Zhou, Xin; Zhang, Yi; Tang, Mingyun; Fu, Juan; Deng, Yuqing; Liang, Xin; Zhao, Long; Li, Zhi; Wang, Tiangang; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundDuring severe acute pancreatitis (SAP), damage to the intestinal mucosal barrier and translocation of intestinal pathogenic bacteria are key mechanisms that accelerate the disease progression of SAP. Chaihuang Qingyi Huoxue Granule (CH) is a herbal formula used in the clinical treatment of SAP. This study aims to investigate the role of CH in regulating gut microbiota and intestinal mucosal barrier in SAP rats.MethodsSodium taurocholate (3.5%) was retrogradely perfused into the biliopancreatic duct to establish the model of SAP in rats. CH (4.4 g/kg) was administered by gavage. Serum amylase, lipase, and endotoxin levels were measured. Hematoxylin-eosin (HE) staining was used to observe morphological changes in the pancreas and colon. The expression of zona occludens-1 (ZO-1) and occludin in the colon was examined by immunohistochemistry (IHC) and western blot. 16S rDNA gene sequencing was used to analyze the gut microbiota of the rats. The content of short-chain fatty acids (SCFAs) in the intestinal contents of the rats was determined by gas chromatography-mass spectrometry (GC-MS).ResultsCH reduced serum amylase, lipase, and endotoxin levels in SAP rats, alleviated pathological damage in the pancreas and colon, and restored the expression of ZO-1 and occludin. Moreover, CH alleviated gut microbiota dysbiosis in SAP rats, with restored gut microbiota diversity and structure. At the phylum level, the relative abundance of Firmicutes and Bacteroidetes increased, while that of Proteobacteria decreased. At the genus level, the abundance of Ruminococcus 1, Parabacteroides, Prevotellaceae UCG-001, Lachnospiraceae NK4A136 group, and Lactobacillus increased, while that of Escherichia-Shigella, Enterococcus, and Enterobacter decreased. In addition, CH increased the levels of SCFAs in the intestinal contents of SAP rats.ConclusionCH ameliorates SAP by maintaining the homeostasis and diversity of the gut microbiota, increasing the levels of SCFAs, and repairing the intestinal mucosal barrier.